Swahili epic poerty: a musical study - Jones, A. M. (International Library of African Music, 1975)
While a good deal of attention has been paid by linguists to Swahili epic poetry, which in performance is sung and not spoken, the music has received hardly any treatment. This essay is a study of the music of one of these epics. As far as I know it is the first time that an extended transcription of this music has appeared. Only by having available such transcriptions can we hope to solve the various questions of a musical nature which these epics raise
Keywords: African Music